2006
DOI: 10.1152/ajpheart.01024.2005
|View full text |Cite
|
Sign up to set email alerts
|

Time course analysis of baroreflex sensitivity during postural stress

Abstract: Postural stress requires immediate autonomic nervous action to maintain blood pressure. We determined time-domain cardiac baroreflex sensitivity (BRS) and time delay (tau) between systolic blood pressure and interbeat interval variations during stepwise changes in the angle of vertical body axis (alpha). The assumption was that with increasing postural stress, BRS becomes attenuated, accompanied by a shift in tau toward higher values. In 10 healthy young volunteers, alpha included 20 degrees head-down tilt (-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 56 publications
10
77
0
1
Order By: Relevance
“…14 Afferent, central, and vagal efferent baroreceptor reflex pathways were evaluated by quantifying baroreflex sensitivity using the sequential method. 15 Beat-to-beat values of systolic BP and interbeat interval were interpolated and resampled at 1 second. Cross-correlations were calculated using a 10-second window containing systolic BP for delays in the interbeat interval window of 0 to 5 seconds.…”
Section: Systemic Cardiovascular Controlmentioning
confidence: 99%
“…14 Afferent, central, and vagal efferent baroreceptor reflex pathways were evaluated by quantifying baroreflex sensitivity using the sequential method. 15 Beat-to-beat values of systolic BP and interbeat interval were interpolated and resampled at 1 second. Cross-correlations were calculated using a 10-second window containing systolic BP for delays in the interbeat interval window of 0 to 5 seconds.…”
Section: Systemic Cardiovascular Controlmentioning
confidence: 99%
“…The relationship between spectral components of cardiovascular variabilities and direct measures of muscle sympathetic nerve activity in humans has been shown to correlate closely over a range of arterial pressure changes (37), except when sympathetic activity is reduced (45). In relation to the available techniques, however, it has been reported that spontaneous and pharmacologically determined BRS are complementary (41) and that the BRS methods may contribute to more in-depth examination of the baroreflex circulatory control (59).…”
Section: Orthostatic Stress Response Across 24-h Exercise Trialmentioning
confidence: 99%
“…In that respect, the method can prove useful when tracking transient changes in BRS during sleep, in exacting conditions (exercise, altitude, daily practice e.g., critical care/anesthesia), or during clinical physiology interventions (standing up and tilt responses (Westerhof et al. 2006)). Clearly, no analysis method can pretend, or needs, to cover all the aspects of the cardiac baroreflex with minute precision.…”
Section: Discussionmentioning
confidence: 99%
“…Head‐up tilt reduces BRS by a factor of 2–3 (Westerhof et al. 2006). It thus appears that BRS as a level is highly variable depending on the state a subject is in and xBRS ranges correspond to those found in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation